EIF SME Access to Finance Index - June 2018 Update - Wouter Torfs (European Investment Fund (EIF), 2018)
This EIF Working Paper elaborates on the most recent update of the EIF SME Access to Finance (ESAF) Index, a composite indicator used to monitor SME external financing markets in the 28 EU countries. The current update, using latest available data, constitutes the fifth iteration of this exercise. The paper is used to provide some background information underlying the aggregate ESAF results, by analysing its four subindices and their subindicators and focussing on a select number of individual results.
Keywords: 330